Effect of Operating Costs, Total Debt, and Sales Volume on Net Profit (Study on Coal Sub-Sector Mining Companies Listed on the Indonesia Stock Exchange for the 2017-2019 Period) - Leny Suzan; Nikita Melisa Siallagan (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this study is to test and provide an analysis of the effect of operating costs, total debt, and sales volume on net income in coal sub-sector mining companies listed on the Indonesian stock exchange for the 2017-2019 period. In this study there were 22 companies. The technique used is purposive sampling and the number of samples that meet the criteria are 12 companies with a period of 3 years. The research method used is descriptive quantitative and uses secondary data derived from the company's financial statements, while the model used to test the research is panel data regression. The results of the study state that simultaneously operating costs, total debt, and sales volume affect the net profit of coal sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period by 83.9246%. Partially, it shows that the operational cost variable has a significant negative effect on net income and sales volume has a significant positive effect on net income, while total debt has no partial effect on net income.